Ultrafine particles, blood pressure and adult hypertension: a population-based survey in Northeast China. (3rd September 2021) - Lin, Li-Zi; Gao, Meng; Xiao, Xiang; Knibbs, Luke D; Morawska, Lidia; Dharmage, Shyamali C; Heinrich, Joachim; Jalaludin, Bin; Lin, Shao; Guo, Yuming; Xu, Shu-Li; Wu, Qi-Zhen; et al.
Abstract: The toxicity of ultrafine particles (UFPs) on blood pressure (BP) has not been well studied. We aimed to evaluate the associations of long-term UFP exposure with different components of BP and the risk of prehypertension/hypertension. We included a total of 24 845 Chinese adults (18–74 years old) in a cross-sectional survey (Liaoning province, China). The 4 year (2006–2009) average concentrations of UFP was estimated using a chemical transport model. We measured systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP) and pulse pressure (PP), prehypertension and hypertension. We used a generalized linear mixed model to examine the associations while controlling for important individual covariates. One unit (1 μ g m −3 ) increase in UFP was associated with an increase in SBP of 1.52 mm Hg [95% confidence interval (CI): 0.48–2.55], DBP of 0.55 mm Hg (95% CI: 0.01–1.08) in DBP, MAP of 0.92 mm Hg (95% CI: 0.23–1.61) and PP of 0.62 mm Hg (95% CI: 0.05–1.20). The UFP-BP associations were stronger in women than in men. One unit increase in UFP was associated with an increased risk of hypertension and prehypertension (OR = 1.23, 95% CI: 1.09–1.38; OR = 1.12, 95% CI: 1.04–1.21) compared to normotension group, and these associations were stronger in overweight/obese participants. Our study showed that long-term exposure to UFP was associated with elevated BP and higher odds of hypertension. These findings suggest that strategies to monitor and reduce UFPs, which are not a regulated pollutant, could have beneficial cardiovascular effects.